The Politics of Civil Society in the Post-Suharto Indonesia: NGOs and CSOs Relations - Bob S. Hadiwinata (Centre for Public Policy and Management Studies, 2003)
Hopes for democratization in Indonesia runs high, especially among political observers both at home and abroad. However, the elitist character of Indonesian politics have produced surprises and volatile changes that in the long run may jeopardize democracy itself. When decentralization was introduced, the power falls into the hands of the local bosses whose greed control on local resources have brought local political system into stalemate. When most parts of the society took laws into their own hands, the concept of civil society is inflated and mischievousness enters the local politics.